Exploring the Future of America’s Digital Workspace Solutions - Hossain, Md Azhad; Das, Srabani; Suha, Samia Hasan; Noor, Syeda Kamari; Imran, MD Ahsan Ullah; Aziz, Mustakim Bin; ., RAIYAN (Journal of Ecohumanism, 2025)
Digital workplace transformation has considerably more profound implications when redesigning a workplace than deciding which technologies to use or not. Not only will the equipment utilized in work activities change in the future due to digital work, but working activities and processes themselves will frequently alter as well. Employee psychological requirements, such as the desire for relatedness, competence, and autonomy, are significant in this setting because they influence the employees’ willingness to embrace their new workplace. More precisely, employees will be more inclined to embrace digital transformation if they believe that working in a digital environment would make it easier for them to achieve higher performance, greater happiness, and personal well-being. Therefore, this study aims to ascertain if employee participation, well-being, and support for digital work contribute to the workplace’s digital transformation. By doing this, we bridge a gap in the research and provide evidence that the interpersonal relatedness of employees in a digital work environment significantly impacts their performance and overall well-being. Employee intentions to support the shift to a digital workplace are subsequently increased. To meet the difficulties of digital transformation, we hope this study will assist pre-digital organizations in reevaluating their plans in light of employee participation. The report also invites researchers to use missing value analysis to examine whether and how those parameters are formed differently in light of the COVID-19 pandemic scenario in the northern state of the USA.